EFFICACY OF ATORVASTATIN IN REDUCING PROTEINURIA IN PATIENTS OF CHRONIC KIDNEY DISEASE - Rizwan Azam (Army Medical College Rawalpindi, 2019)
Objective: To determine the efficacy of atorvastatin in reducing proteinuria in patients of chronic kidney disease.